Micro check valves for integration into polymeric microfluidic devices - Wong, Kok-Keong (2012)
In this paper we describe the design, simulation, fabrication and characterization of micro check valves suitable for integration into polymeric microfluidic devices such as micropumps or test cartridges for biomedical analysis. The valves are fabricated by a polymeric surface micromachining process, which utilizes SU-8 as the functional material. The devices are assembled with the lamination technique. A micro check valve consists of three layers: an inlet layer, a valve layer and an outlet layer. The valve is a disc with a diameter of 1 mm. The disc is suspended on folded beams, which act as valve springs. Both valve disc and springs are fabricated in a 100 µm SU-8 layer. The valves prove a clear flow rectification function. Relatively low pressure is required for opening the valve. The valves were tested and characterized with water. One of the valves is successfully integrated into a polymeric micropump. These valves prove the facile and reliable lamination technology for the fabrication of complex polymeric microfluidic devices for biomedical analysis.